del Nido versus St. Thomas’ blood cardioplegia in the young (DESTINY) trial: protocol for a multicentre randomised controlled trial in children undergoing cardiac surgery - Massimo Caputo; Serban Stoica; Kelly Handley; Timothy J Jones; Nigel E Drury; Barnaby R Scholefield; Martin Kostolny; Alex Robertson; Yongzhong Sun; Carin Van Doorn; Warwick B Dunn; John V Pappachan; et al. (BMJ Open)
Introduction Myocardial protection against ischaemia–reperfusion injury is a key determinant of heart function and outcome following cardiac surgery in children. However, myocardial injury still occurs routinely following aortic cross-clamping, as demonstrated by the ubiquitous rise in circulating troponin. del Nido cardioplegia was designed to protect the immature myocardium and is widely used in the USA but has not previously been available in the UK, where St. Thomas’ blood cardioplegia is most common. The del Nido versus St. Thomas’ blood cardioplegia in the young (DESTINY) trial will evaluate whether one solution is better than the other at improving myocardial protection by reducing myocardial injury, shortening ischaemic time and improving clinical outcomes.Methods and analysis The DESTINY trial is a multicentre, patient-blinded and assessor-blinded, parallel-group, individually randomised controlled trial recruiting up to 220 children undergoing surgery for congenital heart disease. Participants will be randomised in a 1:1 ratio to either del Nido cardioplegia or St. Thomas’ blood cardioplegia, with follow-up until 30 days following surgery. The primary outcome is area under the time–concentration curve for plasma high-sensitivity troponin I in the first 24 hours after aortic cross-clamp release. Secondary outcome measures include the incidence of low cardiac output syndrome and Vasoactive-Inotropic Score in the first 48 hours, total aortic cross-clamp time, duration of mechanical ventilation and lengths of stay in the paediatric intensive care unit and the hospital.Ethics and dissemination The trial was approved by the West Midlands—Coventry and Warwickshire National Health Service Research Ethics Committee (21/WM/0149) on 30 June 2021. Findings will be disseminated to the academic community through peer-reviewed publications and presentation at national and international meetings. Parents will be informed of the results through a newsletter in conjunction with a national charity.Trial registration number ISRCTN13638147; Pre-results.